THE USE OF COMMUNICATION STRATEGIES BY THE TEACHER IN ESP CLASS AT UNIVERSITY OF MUHAMMADIYAH MALANG - Fahrinawati (Institut Agama Islam Darul Ulum Kandangan, 2020)
Teaching in the classroom by using English has raised the problem. The students faced the problem to understand the teacher’s talk because of lack of vocabulary. In order to solve this, the teachers are able to communicate to the students actively by using their hands, imitating sound, inventing new words, or describing what they mean. These ways of communicating are called communication strategies (CSs). EFL teachers are not always aware of the importance of teaching communication strategies to their students or, if they are aware, they do not explicitly train their students to use them. They do not use these strategies themselves to serve as a model to their students. This study investigated the communication strategies used by the teacher in ESP Class and the potential factors that influence the communication strategies they use in the class. The data came from three sources: (1) Transcription from audio recording of the teacher in teaching and learning process. (2) Interview with the teacher. (3) And observation note taking during the process of teaching. The results indicated that the most frequently communication strategy used by the teacher in class is code-switching, and learning activity, students’ comprehending and teacher’ habit are factors that influenced the communication strategies used.